A composite indicator for the waste management in the EU via Hierarchical Disjoint Non-Negative Factor Analysis. (February 2021) - Cavicchia, Carlo; Sarnacchiaro, Pasquale; Vichi, Maurizio
Abstract: In the last years, the quantity of information and statistics about waste management are more and more consistent but so far, few studies are available in this field. The goal of this paper is of producing a model-based Composite Indicator of "good" Waste Management, in order to provide a useful tool of support for EU countries' policy-makers and institutions. Composite Indicators (CIs), usually, are multidimensional concepts with a hierarchical structure characterized by the presence of a set of specific dimensions, each one corresponding to a subsets of manifest variables. Thus, we propose a CI for Waste Management in Europe by using a hierarchical model-based approach with positive loadings. This approach guarantees to comply with all the good properties on which a composite indicator should be based and to detect the main dimensions (i.e., aspects) of the Waste Management phenomenon. In other terms, this paper provides a hierarchically aggregated index that best describes the Waste Management in EU with its main features by identifying the most important high order (i.e., hierarchical) relationships among subsets of manifest variables. All the parameters are estimated according to the maximum likelihood estimation method (MLE) in order to make inference on the parameters and on the validity of the model. Highlights: Composite Indicator is a unobservable latent variable useful to summarize information. Waste management is crucial for the environmental and for the human life in general. Composite Indicator for the Waste management in EU with its main aspects.